Facilitating the safety evaluation of manufactured nanomaterials by characterising their potential genotoxic hazard: final publishable report - Nanogenotox Partners (2013)
Nanotechnology is a highly strategic industrial and economic sector showing enormous potential benefits for many societal and environmental domains. Human exposure to manufactured nanomaterials (MNs)present in consumer products may occur during several phases of their life cycle, from synthesis, production and inclusion in the products to the release of MNs into the environment. The lack of scientific knowledge and the absence of evidence demonstrating the safety of some nanomaterials make regulation a challenge. In 2009 the Executive Agency for Health and Consumers (EAHC) awarded a grant through the second programme of Community action in the field of health (2008-2013) for a Joint Action (JA) on the “Safety of nanomaterials”. The NANOGENOTOX Joint Action started in March 2010 for a period of 3 years and had a total budget of over 6.2 million euros, 46% co-funded by the European Commission’s Health Programme. It was coordinated by the French Agency for Food, Environmental and Occupational Health & Safety (ANSES). Sixteen associated partners from 11 member states and 13 collaborating partners came together to pool their expertise and competences.